Are management-based regulations effective? Evidence from state pollution prevention programs - Bennear, Lori Snyder (Journal of policy analysis and management, 2007)
This paper evaluates a recent innovation in regulating risk called management-based regulation. Traditionally, risk regulation has either specified a particular means of achieving a risk-reduction goal or specified the goal and left the means of achieving that goal up to the regulated entity. In contrast, management-based regulation neither explicitly imposes the means, nor the ends. Rather, what is required is that each regulated entity review its production processes and develop a set of goals and procedures that will reduce risk. I evaluate the effectiveness of management-based regulation by taking advantage of policy variation that occurred when 14 states adopted such regulations for toxic chemical control in the 1990s. Using panel data for just over 31,000 manufacturing plants in the United States, I investigate whether facilities subject to management-based regulations had larger changes in total quantities of toxic chemical releases, engaged in more pollution prevention activities, or reported fewer toxic chemicals to the Toxics Release Inventory (TRI). The results indicate that management-based regulation has had a measurable positive effect on the environmental performance of manufacturing plants. In particular, plants subject to management-based regulation experienced larger decreases in total pounds of toxic chemicals released and were more likely to engage in source reduction activities.